CONVEXITY AND MONOTONICITY FOR ELLIPTIC INTEGRALS OF THE FIRST KIND AND APPLICATIONS - Yang, Zhen-Hang; Tian, Jing-Feng (Applicable analysis and discrete mathematics, 2019)
In the paper, by virtue of two new tools, the authors present the monotonicity and convexity of certain combinations of the complete elliptic integrals of the first kind, and obtain new sharp bounds and inequalities for them.